2018
DOI: 10.4317/medoral.22466
|View full text |Cite
|
Sign up to set email alerts
|

Autologous dental pulp mesenchymal stem cells for inferior third molar post-extraction socket healing: A split-mouth randomised clinical trial

Abstract: BackgroundSince the discovery of adult mesenchymal stem cells extensive research has been conducted to determine their mechanisms of differentiation and effectiveness in cell therapy and regenerative medicine.Material and MethodsTo assess the efficacy of autologous dental pulp mesenchymal stem cells delivered in a collagen matrix for post-extraction socket healing, a single-centre, double-blind, randomised, split-mouth, controlled clinical trial was performed. Both impacted mandibular third molars were extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 17 publications
(28 reference statements)
0
26
1
Order By: Relevance
“…All three studies conclude that the application of DPSC to bone periodontal disease shows significant improvement in a clinical setting with no observed adverse effects. Barbier et al, however, observed no significant difference in mandibular post extraction socket healing resulting from use of DPSC [54]. Also in this study, bone density nor interdental septum height were found to be significantly increased by the addition of DPSC [54].…”
Section: Current Clinical Applicationscontrasting
confidence: 72%
“…All three studies conclude that the application of DPSC to bone periodontal disease shows significant improvement in a clinical setting with no observed adverse effects. Barbier et al, however, observed no significant difference in mandibular post extraction socket healing resulting from use of DPSC [54]. Also in this study, bone density nor interdental septum height were found to be significantly increased by the addition of DPSC [54].…”
Section: Current Clinical Applicationscontrasting
confidence: 72%
“…Furthermore, investigation into the natural opening of pores following in vivo degradation is needed to ascertain the changes in porosity over time. ‘Minimally manipulated’ MSC sources should be examined, where BMA, the current surgical gold standard, or periosteum micrografts, MSCs released from macerated tissue, could be combined with PCL3%-E [ 67 , 68 , 69 ]. Additionally, future in vivo studies are required to not only detail membrane degradation in vivo, but also to characterise the membranes influence on bone regeneration [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…A total number of seven publication reported on the clinical use of dentals stem cells or the use of dental stem cells as an intervention (Figure 7) [496][497][498][499][500][501][502]. The majority of the identified publications focus on dentistry; in detail, publications evaluated the role of dental stem cells in third molar post-extraction socket healing [496], the role of autologous periodontal ligament stem cells' periodontal intrabony defects using [497], the role of dental stem cells in human intrabony defects [498], and the regeneration dental pulp after implantation into injured teeth [501], respectively. One publication on the clinical uses in dentistry was a case report reporting the grafting of mesenchymal stem cells from dental pulp for the retrieval of a periodontally compromised tooth by allogeneic [500].…”
Section: Current Clinical Trialsmentioning
confidence: 99%
“…Two of the trials were investigating the role of DPSCs to treat COVID-19 [502] (ClinicalTrials.gov Identifier: NCT04336254, NCT04302519), one was investigating the role of DPSCs in a trial for osteoarthritis in the knee (NCT04130100), another was investigating the role of human dental pulp mesenchymal stem cells ischemic stroke (NCT04608838), and one was investigating the role of dental pulp cells for the treatment of diabetes (NCT03912480). Even with the high number of publications about dental stem cells, a low number of publications clinically using dental stem cells were identified [496][497][498][499][500][501][502]. While the in vitro and animal in vivo experiments with DSCs seem promising, there is still plenty left to investigate whether it was concerning cellular behavior, culturing techniques, or choice of scaffolds approaches in order to better the translation of these techniques into clinical settings.…”
Section: Current Clinical Trialsmentioning
confidence: 99%